Metal distribution for sediment samples of the Ludwig Prandtl cruise LP20160725 - Petrauskas, Catharina; Ebeling, Anna; Zimmermann, Tristan; Pieper, Andrea; Irrgeher, Johanna; Pröfrock, Daniel (PANGAEA, 2022)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in the surroundings of offshore wind farms of the German Bight between 25.07.2016 and 02.08.2016. The surface sediment samples were taken by a box grab, homogenized, freeze-dried and wet-sieved to gain the <20 µm grain size fraction. The <20 µm grain size fraction was acid digested and measured by ICP-MS/MS for their (trace) metal mass fractions.